THEORY OF WORK ADJUSTMENT RELATED TO SELF REGULATION AND PSYCOLOGICAL WEEL-BEING ON BK CAREER IN HIGHER EDUCATION - Faris Abdurrahman; Daharnis; Mega Iswari (Yayasan Citra Dharma Cindekia, 2022)
Work not only acts as a source of fulfillment of various basic life needs, but is also part of the identity of an adult individual as well as a vehicle for achievement and self-actualization.TWA defines this as